STABILITAS DIMENSI KAYU MAHANG (Macaranga hypoleuca (Reichb.f.et Zoll.) M.A) BERDASARKAN POSISI KETINGGIAN BATANG DAN SUHU PENGERINGAN - Juheri, .; Usman, Fadillah H; Yani, Ahmad (Universitas Tanjungpura, 2017)
This study aims to determine the effect of stem height position, drying temperature and the interaction of both factors. factorial experiment method in the Completely Randomized Design (RAL) it is consists of two factors treatment with three timer repetitions. Tha’s factor is the Position of the height of the tree trunk that conret of 3 sub factors namely the base of the stem, the middle of the stem and the top of the stem. Drying of Temperature consist of 3 sub factors is 550C, 700C and 850C. The average result of the dimension changiry on the highest radial is in the middle of the stem with the drying temperature 850C is 2.0740% and the lowest is the base of the stem with drying temperature of 700C is 1.0667%. While the highest tangential of dimension is in the base of the stem with drying temperature 550C is 2.9598% and the lowest is in the position of stem with drying temperature 550C is 1.1163%. Based on the research the position of the height stem and the drying temperature is having the real effect, on the dimension of the wood with the height of the stem. However the high of drying temperature is not inflounce no the value of depreciation of ratio. The best Dimension Stability is on the top of the stem, in the drying temperature 550C, with the ratio’s result tangensial depriciation 0,87. While in the dry condition, the lowest ratio’n is in the middle of the stem in 700C temperature is 0.62. Generally the result shows dimensional of stability with the ration tangenial of depreciation is sufficient after drying wood.Keywords : Dimensional Stability, Drying Temperature, Height Position of the stem